Cognitive Labor - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Cognitive labor refers to the mental work associated with anticipating the needs of family members (especially children), identifying options for meeting those needs, deciding among the options, and monitoring the results of those decisions (Daminger 2019). Although distinct from the physical dimensions of unpaid care and domestic labor, like these activities, cognitive labor is viewed in many societies as primarily women’s responsibility. Cognitive labor is, thus, an important component of gender inequality within households. This tool measures cognitive labor in association with different agricultural and non-agricultural activities using easily understandable language (“thinking and planning”). We recommend the use of this tool in the design, monitoring, and evaluation of development programs aimed at improving women’s empowerment and reducing women’s work burdens. This data study includes following files. 1. A survey document (including implementation guidelines). 2. Two files, CAPI_Choices and CAPI_Survey, along with the accompanying files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with others, for constructing a CAPI program ready for survey implementation.